Distribution and linkage of microplastics across a sea ice-linked environment in the northwestern Arctic - Haiyan Yang; Jinfeng Ding; Wei Cao; Jingxi Li; Fenghua Jiang; Zhibo Lu; Chengjun Sun (Environmental Pollution, 2026)

Ionic/hydrogen-bonding dual-network orchestration in sulfonated-OPBI via phytic acid-PEI nanoarchitectonics of PAFs for efficient proton transfer highways - Fei Chen; Xinyi Zong; Xianfeng Guan; Chengjun Song; Zhaoyan Sun; Baijun Liu; Wei Hu (Chemical Engineering Journal, 2026)

Nanofiber ionic bridge framed quasi-solid polymer electrolyte with nanocellulose and PAF for improved low-temperature lithium battery - Jiayi Luo; Shenyuan Li; Yangyang Yu; Chengjun Song; Zhaoyan Sun; Baijun Liu; Wei Hu (Chemical Engineering Journal, 2026)

Distribution characteristics of emerging contaminants and microbial communities in Bohai Sea sediments - Jiale Tian; Lichen Wang; Yutan Wang; Minggang Zheng; Chengjun Sun (Marine Environmental Research, 2026)

Microplastics in two fish species from Prydz Bay and King George Island: Occurrence, characteristics and risk assessment - Kexin Zhang; Zhiwei Gao; Peng Ju; Yunmei Sun; Jie Zhang; Yan Gu; Chengjun Sun; Haitao Ding (Marine Pollution Bulletin, 2026)

Steel plate-UHPC composite strengthening method for large-span prestressed concrete box girder bridges: Simulation, optimization, and case study - Tao Sun; Weikun He; Chengjun Tan; Jiahe An; Junde Hu; Lizhi Lu; Hua Zhao (Engineering Structures, 2026)

Smart optical imaging-assisted acoustic streaming enrichment system for targeted microalgae screening under multiple stress conditions - Yihan Ma; Longfei Chen; Yifan Wang; Tao Jiang; Chen Yang; Xiaotong Si; Yantong Liu; Keyu Chen; Fenghua Jiang; Chengjun Sun; Xuan Xiao; Yi Yang (Bioresource Technology, 2026)

A unified density-aware network for stored-grain pest detection with intelligent risk assessment - Long Chen; Rui Li; Chengjun Xie; Peng Chen; Jie Zhang; Jianming Du; Hongbo Chen; Runsheng Qi; Jiahui Sun (Journal of Stored Products Research, 2026)

Targeted control of beef spoilage: Integrating slaughter-source tracking with packaging-temperature hurdles for precision preservation - Jiarui Li; Dequan Zhang; Ming Tian; Chengjun Min; Debao Wang; Xin Li; Xiaotong Sun; Yanan Tang; Yuxia Qi; Chengli Hou (Food Research International, 2026)

In-situ stress measurements over the Eastern Himalayan syntaxis and implications for seismicity - Xianghui Qin; Chongyuan Zhang; Derek Elsworth; Wen Meng; Zhihao Liang; Chengjun Feng; Yuehui Yang; Dongsheng Sun (Tectonophysics, 2025)

Molecular insights into Yb(III) speciation in sulfate-bearing hydrothermal fluids from X-ray absorption spectra informed by ab initio molecular dynamics - Xiaodong Zhao; Duo Song; Sebastian T. Mergelsberg; Micah P. Prange; Daria Boglaienko; Zihua Zhu; Zheming Wang; Carolyn I. Pearce; Chengjun Sun; Kevin M. Rosso; Xiaofeng Guo; Xin Zhang (Geochimica et Cosmochimica Acta, 2025)

Synergistic bulk and back interface passivation enabled by in situ Ag-doping and Nb-engineering for efficient kesterite solar cells - Wenjie Zhu; Sisi Jia; Jingyi Meng; Chun Guo; Xinyu Zhang; Linxin Gao; Yixiang Xiao; Yanping Song; Jiayong Zhang; Huanhuan Sun; Jin Wang; Shihua Huang; et al. (Chemical Engineering Journal, 2025)

Synergistic dynamic pitch and incoherent scattering enabling programmable cellulose thermochromic hybrids with UV–Vis-NIR broad modulation and multifunctionality - Binhong Yu; Ziyan Chen; Zhiyuan Sun; Chengjun Yu; Zhenni Lu; Songshan Zeng (Chemical Engineering Journal, 2025)

Estimation of Genetic Parameters for Hypoxia Tolerance in the Pacific Oyster, Crassostrea gigas - Mengmeng Xu; Ben Yang; Xiaojie Han; Deqi Sun; Chao Guo; Chengjun Zhi; Qi Li; Shikai Liu (Journal of Ocean University of China, 2025)

Evolutionary history of mixed tree species improved soil nutrient content of Pinus massoniana plantation - Chengjun Yang; Panmei Jiang; Zhuangzhuang Qian; Jinyan Sun; Tonggui Wu; Zhangqi Yang; Yue Sun; Xingzhao Huang (Plant and Soil, 2025)

Genetic Basis of Low-Salinity Tolerance in the Pacific Oyster (Crassostrea gigas) as Revealed by Estimation of Genetic Parameters and Genome-Wide Association Study - Xiaojie Han; Ben Yang; Chao Guo; Mengmeng Xu; Deqi Sun; Chengjun Zhi; Qi Li; Shikai Liu (Marine Biotechnology, 2025)

Low-temperature catalytic oxidation of toluene using CeO2@MIL-101(Fe): Stability against water and SO2 - David Murindababisha; Abubakar Yusuf; Kien-Woh Kow; Yong Sun; Run Pan; Yong Ren; George Zheng Chen; Jianrong Li; Chengjun Wang; Jun He (Process Safety and Environmental Protection, 2025)

A density-point network for dense tiny stored grain pest counting - Runsheng Qi; Rui Li; Jie Zhang; Yi Xia; Jianming Du; Jiahui Sun; Long chen; Chengjun Xie; Hui Zhang; Guangyu Li (Journal of Stored Products Research, 2025)

Interface adsorption characteristics of microplastics on multiple morphological arsenic compounds - Di Zhang; Jingxi Li; Chengjun Sun; Corry Yanti Manullang; Jiaxuan Yin; Wei Cao; Fenghua Jiang (Journal of Hazardous Materials, 2025)

Interlinked water and sediment microplastics in the Laizhou Bay of China - Hong Chen; Fenghua Jiang; Jingxi Li; Wei Cao; Di Zhang; Futao Zhang; Shiliang Wang; Chengjun Sun (Journal of Oceanology and Limnology, 2025)

Microplastic occurrence and hydrodynamic-sedimentary driving effects in the Bohai Strait region of China - Long Zhou; Chengjun Sun; Jingxi Li; Chang Zhao; Jinfeng Ding; Wei Cao; Fenghua Jiang (Science of The Total Environment, 2025)

Erratum to: The effect of typical seawater cations on the adhesion of mussel protein Mefp-1 based on dissipative quartz crystal microbalance - Futao Zhang; Chengjun Sun; Linqing Xie; Fuqian Li; Fenghua Jiang; Jingxi Li (Journal of Oceanology and Limnology, 2025)

The effect of typical seawater cations on the adhesion of mussel protein Mefp-1 based on dissipative quartz crystal microbalance - Futao Zhang; Chengjun Sun; Linqing Xie; Fuqian Li; Fenghua Jiang; Jingxi Li (Journal of Oceanology and Limnology, 2025)

Abundance of microplastics and its ecological risk assessment in coral reef regions of Peninsular Malaysia - Kok Ping Lim; Chengjun Sun; Sumiani Yusoff; Jinfeng Ding; Kar Hoe Loh; Jingxi Li; Phaik Eem Lim (Marine Pollution Bulletin, 2024)

Releasing the power of innovation: How can a double-layer innovation network promote enterprise innovation from a patent perspective? - Zeqian Wang; Chengjun Wang; Xiaoming Sun (Environment, Development and Sustainability, 2024)

Study of pyrene-based covalent organic frameworks for efficient photocatalytic oxidation of low-concentration NO - Zhiyu Xiao; Yong Ren; George Zheng Chen; Yong Sun; Chengjun Wang; Jun He (Journal of Environmental Chemical Engineering, 2024)

Occurrence of microplastics in the Haima cold seep area of the South China Sea - Di Zhang; Jingxi Li; Peng Ju; Wei Cao; Fenghua Jiang; Chengjun Sun (Science of The Total Environment, 2024)

Environmental characteristics of trace metals in seawater from the Ninety East Ridge in the Indian Ocean - Jingxi Li; Di Zhang; Fenghua Jiang; Hong Chen; Wei Cao; Chengjun Sun (Journal of Oceanology and Limnology, 2024)

A novel photoelectrochemical self-screening aptamer biosensor based on CAU-17-derived Bi2WO6/Bi2S3 for rapid detection of quorum sensing signal molecules - Shiliang Wang; Peng Ju; Weixing Liu; Jingtian Chi; Tiantong Jiang; Zhe Chi; Shuai Wang; Ri Qiu; Chengjun Sun (Analytica Chimica Acta, 2024)

Occurrence and distribution of phycotoxins in the Antarctic Ocean - Jiale Tang; Xiuping He; Junhui Chen; Wei Cao; Tongzhu Han; Qinzeng Xu; Chengjun Sun (Marine Pollution Bulletin, 2024)

Identification of organic pollutants and heavy metals in natural rubber wastewater and evaluation its phytotoxicity and cytogenotoxicity - Dayu Zhu; Chengjun Ge; Ying Sun; Huamei Yu; Jun Wang; Hongfei Sun (Chemosphere, 2024)

Facile synthesis of multi-layer Co(OH)2/CeO2-g-C3N4 ternary synergistic heterostructure for efficient photocatalytic oxidation of NO under visible light - Zhiyu Xiao; Hainam Do; Abubakar Yusuf; Hongpeng Jia; Haolun Ma; Shanshan Jiang; Jianrong Li; Yong Sun; Chengjun Wang; Yong Ren; George Zheng Chen; Jun He (Journal of Hazardous Materials, 2024)

Differential evolution with alternation between steady monopoly and transient competition of mutation strategies - Chenxi Ye; Chengjun Li; Yang Li; Yufei Sun; Wenxuan Yang; Mingyuan Bai; Xuanyu Zhu; Jinghan Hu; Tingzi Chi; Hongbo Zhu; Luqi He (Swarm and Evolutionary Computation, 2023)

First evidence of microplastic ingestion by crescent perch (Terapon jarbua) in Malaysia - Kok Ping Lim; Jinfeng Ding; Kar Hoe Loh; Chengjun Sun; Sumiani Yusoff; Shyama Sundari Devi Chanthran; Phaik Eem Lim (Regional Studies in Marine Science, 2023)

Regulation of electrical properties via ferroelectric polarization for high performance Sb2Te3 thermoelectric thin films - Boyu Yang; Yubo Luo; Chengjun Li; Wang Li; Chengwei Sun; Zheng Ma; Yongxin Qian; Xianwei Zeng; Yingchao Wei; Haiqiang Liu; Dan Zhang; Xin Li; et al. (Chemical Engineering Journal, 2023)

Characteristics of dissolved sugars in the Southern Yap Trench from sea surface to hadal zone - Dong Cui; Chengjun Sun; Chaonan Guo; Wei Cao; Fenghua Jiang; Haibing Ding (Journal of Oceanology and Limnology, 2023)

Characteristics of vertical distributions of methane and dimethylsulphoniopropionate in the southern Yap Trench - Yuhuan Huang; Chengjun Sun; Lina Lü; Neal Xiangyu Ding; Liangmin Yu; Guipeng Yang; Haibing Ding (Journal of Oceanology and Limnology, 2023)

Convergence of soil bacterial communities with time and reduction of bacterial interaction complexity in response to meso- and microplastic stress - Lin Yue; Yangbo Liu; Guanhui Li; Hui Deng; Yuanyuan Zhao; Dan Feng; Hongfei Sun; Huamei Yu; Chengjun Ge; Haiying Chen (Journal of Environmental Chemical Engineering, 2023)

A Review of Microplastics in China Marine Waters - Fenglei Gao; Jingxi Li; Jun Hu; Xianguo Li; Chengjun Sun (Journal of Ocean University of China, 2023)

Benefited wastewater utilization via configurable, spatialized, and microorganisms-integrated biophotonic systems - Yantong Liu; Longfei Chen; Le Yu; Jiaomeng Zhu; Fang Wang; Fenghua Jiang; Chengjun Sun; Li Zheng; Yi Yang (Chemical Engineering Journal, 2023)

Visualizing hydrogen peroxide and hydrogen sulfide fluctuations in living cells via dynamic-reversible fluorescent probes - Jinzhu Gao; Rongchen Wang; Kai Yin; Tianli Zhu; Jie Sun; Chengjun Dong; Xuemei Dong; Mengting Zhao; Xianfeng Gu; Chunchang Zhao (Chemical Engineering Journal, 2023)

R-loopAtlas: An integrated R-loop resource from 254 plant species sustained by a deep-learning-based tool - Kuan Li; Zhenzhen Wu; Jincong Zhou; Wei Xu; Ling Li; Chao Liu; Wei Li; Chengjun Zhang; Qianwen Sun (Molecular Plant, 2023)

Trash to treasure: Green synthesis of novel Ag2O/Ag2CO3 Z-scheme heterojunctions with highly efficient photocatalytic activities derived from waste mussel shells - Jiazhen Cao; Peng Ju; Zheyang Chen; Kunpeng Dou; Jingxi Li; Peng Zhang; Zuhao Zhu; Chengjun Sun (Chemical Engineering Journal, 2023)

Intensified gas-phase hydrogenation of acetone to isopropanol catalyzed at metal-oxide interfacial sites - Kun Liu; Yongbin Sun; Jie Feng; Yang Liu; Jian Zhu; Chengjun Han; Changzhi Chen; Tianyi Bao; Xiaoqun Cao; Xiaomin Zhao; Yong Yang; Guofeng Zhao (Chemical Engineering Journal, 2023)

Reconfigurable modular microbiota systems for efficient and sustainable water treatment - Longfei Chen; Yantong Liu; Pengfu Tian; Le Yu; Fang Wang; Hongshan Xu; Yifan Wang; Wei Li; Li Zheng; Fenghua Jiang; Chengjun Sun; Xuming Zhang; et al. (Chemical Engineering Journal, 2023)

Flow pattern transition and wave characteristics of impinging jet flow on a spinning disk reactor - Dongxiang Wang; Chengjun Gu; Cheng Sun; Xiang Ling; Hao Peng; Xinjun Yang; Fangyang Yuan; Jiyun Du; Wei Yu (Chemical Engineering Journal, 2023)

Vertical variations and composition of dissolved free amino acid in the seawater of the Yap Trench in the western Pacific Ocean - Jiaohong Niu; Chengjun Sun; Bo Yang; Lei Xie; Fenghua Jiang; Wei Cao; Yan Chen; Haibing Ding; Yuhuan Huang; Xianchi Gao (Journal of Oceanology and Limnology, 2023)

Interactive effects of high temperature and crude protein levels on growth performance, nitrogen excretion, and fecal characteristics of broilers - Quanwei Liu; Jinghai Feng; Limin Wei; Chengjun Hu; Xinli Zheng; Ruiping Sun; Minhong Zhang (Tropical Animal Health and Production, 2022)

Bioremediation of tetramethyl thiuram disulfide and resource utilization of natural rubber wastewater by WR-2 Bacillus-dominated microbial community - Dayu Zhu; Chengjun Ge; Hongfei Sun; Jun Wang; Liujing He (Environmental Science and Pollution Research, 2022)

Photoaging Characteristics of Disposable Masks under UV Irradiation - Xinhao Liu; Wei Cao; Linqing Xie; Chengjun Sun; Fenghua Jiang (Journal of Marine Science and Engineering, 2022)
The global outbreak of Corona Virus Disease 2019 (COVID-19) has led to an extreme increase in the use of disposable masks. If the used disposable masks are not appropriately disposed of, they will enter the natural environment and lead to environmental pollution. In order to understand the impacts of disposable masks after being disposed of into the natural environment, aging experiments with simulated natural conditions were performed on the outer, inner, and middle layers of the masks to verify the aging characteristics of disposable masks. We analyzed the mechanical behavior, surface morphology, and Fourier Transform Infrared Spectroscopy (FT-IR) spectra of disposable masks treated with different levels of UV irradiation to understand the possible changes in the masks under UV. Results showed that the elongation at break, tensile strength, and maximum force of all three polypropylene (PP) mask layers decreased after UV irradiation, indicating chemical bond breakage. In the process of photoaging, each layer of the disposable masks showed a different degree of microscopic surface changes after UV irradiation, and these changes gradually intensified with the extension of UV exposure time. FT-IR results showed that functional groups, such as hydroxyl and carbonyl groups increased in each layer after UV irradiation. The results of this study support that, although the different layers of the disposable masks are all made of PP, they age differently in the environment. With the ever-increasing number of disposable masks in the environment, we need to further study the aging and degradation of disposable masks to better understand their potential impacts on the environment in the future.

Occurrence and Seasonal Variation of Microplastics in the Effluent from Wastewater Treatment Plants in Qingdao, China - Fenghua Jiang; Menghui Wang; Jinfeng Ding; Wei Cao; Chengjun Sun (Journal of Marine Science and Engineering, 2022)
Wastewater treatment plants (WWTPs) are considered as one of the important sources of microplastics (MPs) in the marine environment. In this paper, the characteristics of MPs in the effluent discharged from five WWTPs in Qingdao, China, in winter and summer were analyzed. The results showed that only fibers and fragments were observed, with fibers as a dominant part. Rayon was the most domain polymer type, followed by Polyethylene terephthalate (PET) and chlorinated polyethylene (CPE). The average sizes of fiber MPs were 1010 ± 924 µm and 610 ± 691 µm in winter and summer, respectively. The contents of rayon were higher in summer than in winter. More small and transparent MPs were observed in summer. Rayon abundances ranged from 4.1 to 19.9 items/L and 33.3 to 116.7 items/L, with 12.3 ± 5.6 items/L and 67.6 ± 30.6 items/L as the average value in winter and in summer, respectively. The abundances of other polymer type MPs were 7.23~19.65 items/L with average value of 12.7 ± 4.7 items/L in winter and 12.0~20.0 items/L with 16.8 ± 4.7 items/L in summer. The daily emissions were estimated as 8.38 × 109~4.25 × 1010 items (9.2~27.8 kg) for rayon and 8.0 × 109~1.2 × 1010 items (7.6~5.3 kg) discharged for the other polymer type MPs from the five WWTPs. The results indicated that the seasonal variation of characteristics and emission of MPs in the effluent from WWTPs was mainly caused by increasing discharge of rayon, which may relate to people’s living habits and tourism activities.

Levels of urinary metabolites of benzene compounds, trichloroethylene, and polycyclic aromatic hydrocarbons and their correlations with socioeconomic, demographic, dietary factors among pregnant women in six cities of China - Jing Zhu; Xuan Zhao; Mi Yang; Bo Zheng; Chengjun Sun; Xiaoli Zou; Zhen Liu; Kouji H. Harada (Environmental Science and Pollution Research, 2022)

Above- and belowground biomass allocation and its regulation by plant density in six common grassland species in China - Yuanfeng Sun; Yupin Wang; Zhengbing Yan; Luoshu He; Suhui Ma; Yuhao Feng; Haojie Su; Guoping Chen; Yinping Feng; Chengjun Ji; Haihua Shen; Jingyun Fang (Journal of Plant Research, 2022)

Current progress on catalytic oxidation of toluene: a review - David Murindababisha; Abubakar Yusuf; Yong Sun; Chengjun Wang; Yong Ren; Jungang Lv; Hang Xiao; George Zheng Chen; Jun He (Environmental Science and Pollution Research, 2021)

A new route to select the referable values of property indicators for normalization and its application in screening polymeric membrane heavy metal (Co, Ni, and Cr)-ion-selective electrodes with multiple high-response performances - Lingzhi Sun; Chengjun Sun; Xianxiang Sun (Environmental Science and Pollution Research, 2021)

New insights into the toxic interactions of polyvinyl chloride microplastics with bovine serum albumin - Peng Ju; Yu Zhang; Jinfeng Ding; Yifan Zheng; Shuai Wang; Fenghua Jiang; Chengjun Sun (Environmental Science and Pollution Research, 2021)

Distribution pattern and geochemical analysis of rare earth elements in deep-ocean sediments - Jingxi Li; Chengjun Sun; Fenghua Jiang; Fenglei Gao; Yifan Zheng (Journal of Oceanology and Limnology, 2021)

Comparative toxicity of five dispersants to test organisms at different trophic levels: Platymonas helgolandica, Ruditapes philippinarum, and Acinetobacter sp. Tox2 - Zhisong Cui; Xiao Luan; Dandan Li; Qian Li; Limei Shuai; Li Zheng; Chengjun Sun; Gaoge Wang (Environmental Science and Pollution Research, 2020)

Vertical variations of dissolved carbohydrates in the North Yap Trench - Chaonan Guo; Chengjun Sun; Guipeng Yang; Honghai Zhang; Yan Chen; Xiaofei Yin; Fenghua Jiang; Yuhuan Huang; Jiaohong Niu; Haibing Ding (Journal of Oceanology and Limnology, 2020)

Towards the understanding from sea surface to hadal zone—A multidisciplinary study of the Yap Trench - Haibing Ding; Chengjun Sun (Journal of Oceanology and Limnology, 2020)

Distribution characteristics of lipids in hadal sediment in the Yap Trench - Yixin Yan; Chengjun Sun; Yuhuan Huang; Wei Cao; Fenghua Jiang; Guipeng Yang; Haibing Ding (Journal of Oceanology and Limnology, 2020)

Comparison of sedimentary organic carbon loading in the Yap Trench and other marine environments - Dong Li; Jun Zhao; Chenggang Liu; Chengjun Sun; Jianfang Chen; Jianming Pan; Zhengbing Han; Ji Hu (Journal of Oceanology and Limnology, 2020)

Geochemical characteristics of hadal sediment in the northern Yap Trench - Yuhuan Huang; Chengjun Sun; Guipeng Yang; Xin’an Yue; Fenghua Jiang; Wei Cao; Xiaofei Yin; Chaonan Guo; Jiaohong Niu; Haibing Ding (Journal of Oceanology and Limnology, 2020)

Water characteristics of abyssal and hadal zones in the southern Yap Trench observed with the submersible Jiaolong - Xuehai Liu; Yongzhi Liu; Wei Cao; Chengjun Sun (Journal of Oceanology and Limnology, 2020)

An integrated measurement of six response performance indicators for lead ion-selective electrodes and application - Lingzhi Sun; Chengjun Sun; Xianxiang Sun (Environmental Monitoring and Assessment, 2019)

Ciliate Uronema marinum is the causative agent of scuticociliatosis in farm raised turbot Scophthalmus maximus - Guangxun Du; Lingyun Qu; Kun Shang; Chengjun Sun; Chen Wang; Ping Gao (Journal of Oceanology and Limnology, 2019)

Migration of phthalates from plastic packages to convenience foods and its cumulative health risk assessments - Jinling Yang; Weizhong Song; Xiaojie Wang; Yongxin Li; Jiannan Sun; Weilei Gong; Chengjun Sun (Food Additives & Contaminants Part B-Surveillance, 2019)

Degradation potential and diversity of oil-degrading bacteria isolated from the sediments of the Jiaozhou Bay, China - Wei Gao; Xiangxing Gao; Tiezhu Mi; Bin Han; Yiran Zhang; Xinzi Li; Xiaofei Yin; Chengjun Sun; Qian Li; Zhisong Cui; Xiao Luan; Zhigang Yu; et al. (Acta Oceanologica Sinica, 2019)

Removal of tetracyclines, sulfonamides, and quinolones by industrial-scale composting and anaerobic digestion processes - Hang Liu; Chengjun Pu; Xiaolu Yu; Ying Sun; Junhao Chen (Environmental Science and Pollution Research, 2018)

Degradation of lipids in seasonal hypoxic seawater under different oxygen saturation - Yunhong He; Chengjun Sun; Wenjuan Li; Gui-Peng Yang; Haibing Ding (Journal of Oceanology and Limnology, 2018)

Study on immobilization of marine oil-degrading bacteria by carrier of algae materials - Yiran Zhang; Wei Gao; Faxiang Lin; Bin Han; Changfei He; Qian Li; Xiangxing Gao; Zhisong Cui; Chengjun Sun; Li Zheng (World Journal of Microbiology and Biotechnology, 2018)

Lipid accumulation and CO2 utilization of two marine oil-rich microalgal strains in response to CO2 aeration - Shuai Wang; Li Zheng; Xiaotian Han; Baijuan Yang; Jingxi Li; Chengjun Sun (Acta Oceanologica Sinica, 2018)

Biomass, nutrient uptake and fatty acid composition of Chlamydomonas sp. ICE-L in response to different nitrogen sources - Meiling An; Yibin Wang; Fangming Liu; Xiaoqing Qi; Zhou Zheng; Naihao Ye; Chengjun Sun; Jinlai Miao (Acta Oceanologica Sinica, 2017)

The study of the adductor muscle-shell interface structure in three Mollusc species - Yaoyao Zhu; Chengjun Sun; Yingfei Song; Fenghua Jiang; Xiaofei Yin; Min Tang; Haibing Ding (Acta Oceanologica Sinica, 2016)

Acclimation of Antarctic Chlamydomonas to the sea-ice environment: a transcriptomic analysis - Chenlin Liu; Xiuliang Wang; Xingna Wang; Chengjun Sun (Extremophiles, 2016)

Protective effects of Lycium barbarum polysaccharide on neonatal rat primary cultured hippocampal neurons injured by oxygen-glucose deprivation and reperfusion - Chen Rui; Li Yuxiang; Hao Yinju; Zhu Qingluan; Wu Yang; Zhao Qipeng; Wang Hao; Ma Lin; Liu Juan; Zhao Chengjun; Jiang Yuanxu; Wang Yanrong; et al. (Journal of Molecular Histology, 2012)

Influence of limited soil on the root distribution and anchorage of Vitex negundo L. - Feng Long; Shaocai Li; Hailong Sun; Chengjun Li (Journal of Mountain Science, 2012)

Oxidative stress protection and the repair response to hydrogen peroxide in the hyperthermophilic archaeon Pyrococcus furiosus and in related species - Kari R. Strand; Chengjun Sun; Ting Li; Francis E. Jenney; Gerrit J. Schut; Michael W. W. Adams (Archives of Microbiology, 2010)